THE STATUS OF MOTHER TONGUES IN KENYA AND CHINA: LESSONS THE TWO COUNTRIES CAN LEARN FROM EACH OTHER (The University of Nairobi Journal of Language and Linguistics, 2023)
This paper is a comparative analysis of the language situations in China and Kenya,intended to identify the important lessons about language management in amulti-ethnic society that the two countries can learn from each other. China hasover 130 languages, with Mandarin Chinese (Hanyu) being a mother tongue toover 90% of the Chinese population. The situation is different in Kenya, which hasover 40 languages, most of which are minority languages. Significant differencesare noted in the areas of language reforms and policy, language developmentagencies, and the treatment of ethnic minority languages. In each of the twocountries, the constitution spells out some of the language concerns and therelevant guidelines for their usage and management. In Kenya, additional legaltexts about the language policy are currently in preparation. The greatest lessonthat Kenya can learn from China is the need to insist on catering for issues to dowith language at the national government level, resisting any pressure from thecounty governments regarding variations on the relevant constitutional provisions(Republic of Kenya, 2010). The drafters of the Constitution of Kenya 2010 got thisright by giving the national government the function of managing “Languagepolicy and the promotion of official and local languages” (Fourth Schedule, Part 1(5)). The national government must learn from China to treat this as a seriousnational responsibility by formulating the relevant policy guidelines and enactingthe necessary supportive laws. For China, the greatest lesson to learn is the needto also include NGOs and individual efforts in the development of languages.